Emergence of Quantum Critical Behavior in Metallic Quantum-Well States of Strongly Correlated Oxides. Issue 1 (December 2017) - Kobayashi, Masaki; Yoshimatsu, Kohei; Mitsuhashi, Taichi; Kitamura, Miho; Sakai, Enju; Yukawa, Ryu; Minohara, Makoto; Fujimori, Atsushi; Horiba, Koji; Kumigashira, Hiroshi
Abstract Controlling quantum critical phenomena in strongly correlated electron systems, which emerge in the neighborhood of a quantum phase transition, is a major challenge in modern condensed matter physics. Quantum critical phenomena are generated from the delicate balance between long-range order and its quantum fluctuation. So far, the nature of quantum phase transitions has been investigated by changing a limited number of external parameters such as pressure and magnetic field. We propose a new approach for investigating quantum criticality by changing the strength of quantum fluctuation that is controlled by the dimensional crossover in metallic quantum well (QW) structures of strongly correlated oxides. With reducing layer thickness to the critical thickness of metal-insulator transition, crossover from a Fermi liquid to a non-Fermi liquid has clearly been observed in the metallic QW of SrVO3 byin situ angle-resolved photoemission spectroscopy. Non-Fermi liquid behavior with the critical exponentα  = 1 is found to emerge in the two-dimensional limit of the metallic QW states, indicating that a quantum critical point exists in the neighborhood of the thickness-dependent Mott transition. These results suggest that artificial QW structures provide a unique platform for investigating novel quantum phenomena in strongly correlated oxides in a controllable fashion.